PEDAGOGICAL TECHNOLOGIES AS A MEANS OF INCREASING THE EFFECTIVENESS OF TEACHING MATHEMATICS - Lola Urinboyeva; Ahmadjon Sagdullayev (Bright Mind Publishing, 2025)
The article presents a number of measures that should be taken to introduce digital technologies and modern methods into the teaching process in order to implement the strategic goals and objectives of the development of mathematics education, and reveals their importance.
Keywords: Mathematical literacy, critical, creative and systematic thinking, intellectual abilities, technology, pedagogical technology, digital and modern technologies.